2021
DOI: 10.3390/cancers13174285
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Guided Axillary UltraSound (MagUS) Sentinel Lymph Node Biopsy and Mapping in Patients with Early Breast Cancer. A Phase 2, Single-Arm Prospective Clinical Trial

Abstract: Lymph Node Dissection (SLND) is standard of care for diagnosing sentinel lymph node (SLN) status in patients with early breast cancer. Study aim was to determine whether the combination of Superparamagnetic iron oxide nanoparticles (SPIO) MRI-lymphography (MRI-LG) and a Magnetic-guided Axillary UltraSound (MagUS) with biopsy can allow for minimally invasive, axillary evaluation to de-escalate surgery. Patients were injected with 2 mL of SPIO and underwent MRI-LG for SN mapping. Thereafter MagUS and core needle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…This study also looked at the timing of the injection and found that SPIO injections performed at a median of 16 days prior to SLND obtained a better identification rate ( p = 0.031) and higher lymph node retrieval rate ( p < 0.001) compared to injections on the morning of surgery. Other studies also suggested feasibility of preoperative injection up to weeks or months prior to surgery [ 22 , 23 , 29 ]. Although this study had been designed before these publications and examined preoperative injection up to 24 h, a longer waiting period might further reduce required injection volume of magnetic particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also looked at the timing of the injection and found that SPIO injections performed at a median of 16 days prior to SLND obtained a better identification rate ( p = 0.031) and higher lymph node retrieval rate ( p < 0.001) compared to injections on the morning of surgery. Other studies also suggested feasibility of preoperative injection up to weeks or months prior to surgery [ 22 , 23 , 29 ]. Although this study had been designed before these publications and examined preoperative injection up to 24 h, a longer waiting period might further reduce required injection volume of magnetic particles.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative injection more than one day, up to months, prior to surgery needs to be investigated in the future as well, to see if a longer waiting period facilitates more accumulation of iron in the SLNs and/or leads to complicating accumulation in secondary and tertiary nodes. In a recent study, patients were injected with SPIO prior to neoadjuvant chemotherapy, and MRI lymphography was compared before and after chemotherapy with a median of 130 days interval [ 29 ]. As a result, SPIO accumulation was observed in the same lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“… 19 The SLN nodules turned brown or black, and the MRI signal increased (Figure 3 ). 20 On SPIO‐enhanced MRI, metastatic positive SLN showed high‐signal‐intensity area, and negative SLN showed low signal intensity. Studies have shown that the sensitivity, specificity and accuracy of SPIO‐enhanced MRI at 1.5 T with fat‐suppressionsequence in diagnosing SLN metastasis are 100%, 96%, and 96%, respectively.…”
Section: Magnetic Tracer Methodsmentioning
confidence: 99%
“…(A) SLN before injection. (B) SLN enhanced after injection of SPIO (red circle). Source : Reference [20]. Copyright permission obtained…”
Section: Magnetic Tracer Methodsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: the current nanopharmaceuticals for cancer therapy in clinical assays [ 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 ].…”
mentioning
confidence: 99%